Analysis of Students’ Mathematical Problem Solving Ability Based on Self-Efficacy and Gender (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aimed to describe students' mathematical problem solving ability based on self-efficacy and gender. The method used is descriptive qualitative through the provision of self-efficacy questionnaires, tests, interviews, and documentation. Six subjects were selected based on three levels of self-efficacy and gender from a total of 103 students in one class XI MIPA from three different schools. Research subjects were determined using a purposive sampling technique based on the Rasch model analysis. The test results of the subjects were analyzed using four Polya stages consisting of understanding the problem, making a plan, carrying out the plan, and looking back. The results of this study indicate that (1) subjects with high levels of self-efficacy can fulfill all indicators systematically, confidently, and never give up where females are better than males; (2) subjects with medium levels of self-efficacy can fulfill three indicators well and confident, in which males are better than females; (3) subjects with low levels of self-efficacy only fulfill one indicator at making a plan which showed an attitude of giving up and not being confident, where females were better than males.